Measurements of deposited aerosol dose in infants and small children - Corcoran, Timothy E. (Ann Transl Med, 2021)
Pediatric patients are very dependent on inhaled aerosol medications. There are significant differences in how these aerosols deposit in the lungs of children vs. adults that may affect the efficacy of the therapies. Inefficient aerosol delivery to children, caused by factors such as high mouth and throat deposition during oral inhalation, significant losses within adjunct devices such as masks, and high rates of nasal deposition during cannula delivery, can lead to dosing that is difficult to control. Here we discuss the methods, such as deposition scintigraphy, that are used to assess inhaled dose in vivo and review previous studies where these techniques have been applied to measure dosing in children. This includes studies of nebulizers and metered dose inhalers and delivery through adjuncts such as facemasks and nasal cannulas. We discuss the factors that can lead to inefficient inhaled drug delivery and high levels of mouth and throat deposition in children. Finally, we propose areas of innovation to improve inhaled drug delivery to this population. There is a need for child-specific technologies for inhaled drug delivery. This includes the use of smart devices that can guide pediatric breathing patterns and better engage children during treatments, the use of smaller aerosols which are less likely to deposit in the upper airways after inhalation, and the design of better nasal cannula interfaces for aerosol delivery to infants.